Is Telemedicine the Preferred Visit Modality in Patients with Type 1 Diabetes? - Kirzhner, Alena; Zornitzki, Taiba; Ostrovsky, Viviana; Knobler, Hilla; Schiller, Tal (Experimental and Clinical Endocrinology & Diabetes, 2021)
Background The COVID-19 pandemic limits access to diabetes clinics. Remote communication by phone calls and WhatsApp messages became available in the past years. However, the current need to avoid face-to-face meetings necessitates further expansion of telemedicine services. There are limited data whether the option of virtual meetings is a preferred therapeutic modality for patients with type 1 diabetes (T1D).Objective To assess in a cohort of T1D patients, their preference and perception of telemedicine. Methods T1D patients who are followed in a hospital-affiliated diabetes clinic were asked to fill a structured questionnaire aimed to determine their attitude towards telemedicine and their preference of virtual versus conventional visits. The questionnaire was offered to consecutive T1D patients who visited the clinic between August to October 2020.Results Seventy one T1D patients that fulfilled the questionnaire were included. Median age was 38 years, 39% were male, and median duration of diabetes was 18 years. Fourteen percent of the participants preferred only virtual visits, 24% only conventional visits and 62% preferred a combination of these modalities. Sex, origin, education, duration of diabetes, mode of insulin treatment and distance from the clinic were not associated with patients' preference, but older patients (≥ 61 years) tended to prefer conventional visits. Sixty-six percent felt confident in their ability to download data from their personal medical devices. Conclusions Patients from a wide range of treatment modalities are willing to use telemedicine. However, virtual meetings cannot fully replace conventional visits in T1D especially in the older age group.